A network meta‐analysis on the efficacy and safety of monotherapies for tinea capitis, and an assessment of evidence quality. Issue 6 (8th September 2020) - Gupta, Aditya K.; Bamimore, Mary A.; Renaud, Helen J.; Shear, Neil H.; Piguet, Vincent
Abstract: Various monotherapies exist for tinea capitis; however, their relative efficacies have never been determined using a statistical approach which compares treatments' efficacy simultaneously. The goal of this study was to determine the relative efficacy (mycologic and complete cure rates) of monotherapies for the treatment of tinea capitis. On October 5, 2019, searches were performed in Scopus, PubMed, EMBASE, MEDLINE (Ovid), and CINAHL; there were no date restrictions. For the main network meta‐analysis, eligible studies were randomized trials that investigated the effect of tinea capitis monotherapies on subjects' mycological and complete cure rates. Network meta‐analyses were conducted in accordance with the 2015 Preferred Reporting Items for Systematic Reviews and Meta‐Analyses checklist for network meta‐analyses. Mycological cure rate was the primary outcome; complete cure rate and adverse events were secondary outcomes. Twelve studies met the eligibility criteria for the main network; five systemic monotherapies were identified, griseofulvin, ketoconazole, terbinafine, itraconazole, and fluconazole. When the causative species was of the Microsporum genus, griseofulvin was most efficacious in terms of mycological cure (SUCRA = 66.1%) and complete cure (SUCRA = 80.6%). For tinea capitis caused by the Trichophyton species, terbinafine was the most efficacious in terms of both mycological and complete cure (SUCRA values of 75.2% and 78.2%, respectively). Risk of adverse events did not significantly differ across the interventions. Our results are congruent with those of previous pairwise meta‐analyses; our findings also corroborate clinical experience and anecdotal evidence.